Hypermethylation of p16 and DAPK promoter gene regions in patients with non-invasive urinary bladder cancer - Jabłonowski, Zbigniew (Termedia Publishing House, 2011)
INTRODUCTION: The aim of the study was to examine the frequency of methylation status in promoter regions of p16 and DAPK genes in patients with non-invasive bladder cancer. MATERIAL AND METHODS: Forty-two patients (92.9% men, 73.8% smokers, 71.4% T1G1, 19.1% T1G2, 9.5% T1G3) and 36 healthy controls were studied. Isolation of genomic DNA from blood serum and methylation-specific PCR (MSP) were applied. Methylation status – methylated and unmethylated promoter regions of p16 and DAPK genes were analysed. RESULTS: Seventeen out of 42 patients (40.5%) had the methylated p16 gene, while methylation of the DAPK gene was seen in 27 of 42 cases (64.3%). In 12 patients (28.6%) both analysed genes were methylated. A statistically significant (p = 0.046) higher frequency of DAPK gene methylation (71.4%) was observed in patients with lower grade (G1) bladder cancer. CONCLUSIONS: Detection of the aberrant hypermethylation of DAPK and p16 genes in blood DNA from non-invasive bladder cancer patients might offer an effective means for earlier auxiliary diagnosis of the malignancy.